2023
DOI: 10.1021/acsnano.3c06025
|View full text |Cite
|
Sign up to set email alerts
|

Colon-Accumulated Gold Nanoclusters Alleviate Intestinal Inflammation and Prevent Secondary Colorectal Carcinogenesis via Nrf2-Dependent Macrophage Reprogramming

Cao Lu,
Liyuan Xue,
Kaidi Luo
et al.

Abstract: Inflammatory bowel disease (IBD) is one of the main factors leading to colitis-associated colorectal cancer (CAC). Therefore, it is critical to develop an effective treatment for IBD to prevent secondary colorectal carcinogenesis. M2 macrophages play crucial roles in the resolution phase of intestinal inflammation. However, traditional drugs rarely target intestinal M2 macrophages, and they are not easily cleared. Gold nanoclusters are known for their in vivo safety and intrinsic biomedical activities. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Under normal physiological conditions, the Nrf2 in cells binds to the kelch-like ECH-associated protein 1 (Keap1) in the cytoplasm and remains in a steady state; when Keap1 receives an oxidative stress signal, it can release Nrf2 and then transfer it to the nucleus and upregulate the expression of downstream antioxidant proteins, such as HO-1 ( Ibrahim et al, 2023 ). At the same time, HO-1 can also block the NF-κB activation and downregulate the transcription of inflammatory factors and chemokines by inhibiting the production of cytokines and ROS ( Wang and He, 2022 ); this may contribute to the treatment of IBD by inhibiting intestinal inflammation-cancer transformation ( Lu et al, 2023 ).…”
Section: Discussion On the Common Molecular Mechanism Of Sishen Pill ...mentioning
confidence: 99%
“…Under normal physiological conditions, the Nrf2 in cells binds to the kelch-like ECH-associated protein 1 (Keap1) in the cytoplasm and remains in a steady state; when Keap1 receives an oxidative stress signal, it can release Nrf2 and then transfer it to the nucleus and upregulate the expression of downstream antioxidant proteins, such as HO-1 ( Ibrahim et al, 2023 ). At the same time, HO-1 can also block the NF-κB activation and downregulate the transcription of inflammatory factors and chemokines by inhibiting the production of cytokines and ROS ( Wang and He, 2022 ); this may contribute to the treatment of IBD by inhibiting intestinal inflammation-cancer transformation ( Lu et al, 2023 ).…”
Section: Discussion On the Common Molecular Mechanism Of Sishen Pill ...mentioning
confidence: 99%
“…Remarkably, GA exhibited targeted accumulation in the colon. GA not only facilitated M2 differentiation of IL-4-treated peritoneal macrophages but also shifted macrophage polarization from M1 to M2 in a pro-inflammatory setting 239 .…”
Section: Anti-inflammatory Nanotherapeuticsmentioning
confidence: 98%
“…The outcomes demonstrated that the Au NP was more effective in reducing tissue degeneration and inhibiting the p38α enzyme compared to standard Captopril therapy 238 . Shifting macrophage polarization from M1 to M2 plays key roles in resolving inflammation 239 . Lu et al invented glutathione-protected gold nanoclusters (GA) for treating IBD 239 .…”
Section: Anti-inflammatory Nanotherapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione-capped gold nanoclusters were chosen as luminescent materials because of their abundant surface functional groups ( e.g. , the carboxyl and amino groups), good biocompatibility 12 and small average size. 13 ZIF-8 was selected as a carrier with high surface area, good stability, and negligible cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%